Probiotic effect of Streptococcus dentisani on oral pathogens: an in vitro study (2024)
Eng: Probiotics, including Streptococcus dentisani, have been proposed as an alternative to reestablish the ecology of the oral cavity and inhibit the formation of pathogenic biofilms. The main objective of this work was to assess the probiotic ability of S. dentisani against Streptococcus mutans, Streptococcus mitis, and Candida albicans biofilms. The ability of the strains to form a monospecies biofilm and the probiotic potential of S. dentisani using the competition, exclusion, and displacement strategies were determined. All strains were moderate biofilm producers. The ability of S. dentisani to compete with and exclude S. mutans and S. mitis during biofilm formation was not significant. However, S. dentisani significantly reduced pathologic streptococcal biofilms using the displacement strategy. Also S. dentisani reduced the formation of the C. albicans biofilm mainly through competition and displacement. In vitro, S. dentisani exhibited probiotic potential to reduce the formation of potentially pathogenic biofilms. Further investigation is required to understand the biofilm-inhibiting mechanisms exhibited by this probiotic strain.